Analisis Gerakan Tendangan Ap Chagi Pada Taekwondoin junior Putra Kabupaten lombok Timur - NOPI HARI ADI (Universitas Negeri Semarang, 2016)
The "Ap Chagi" kick is a basic kick technique that a Takwondoin must muster it and able to give three point (WTF competition rules & interpretation, 2012:22) This research is a descriptive quantitative research and an action research (if reviewed from the approach of the research). Instruments of the research was using Dartfish Handycam Software and Laptop. Data analysis was using analyzer on Dartfish Software and assesment from the expert judgement consisting angle of hand, angle of back, angle of opened leg and angle of rotation of foot sole and also speed of kick and accuracy of target. From 3 athletes who become subjet of the research, 1 athlet obtained the best result, on the "Ap Chagi" kick the best result was obtained on subject of the research AKB. Result of the research concluded improvement of the form of assistance and referrals movement of researchers, trainers and expert judgment, in the form of physical exercise and practice basic techniques Ap Chagi kick. And result that the ap chagi kick is most excellent or effective in reflection III. It was known that on the Taekwondoin AKB with time 0,34 s, distanca of kick and target 1,60 m, so resultin velocity 5,0 m/s. next, for angle of hand 51,3°, angle of back 141,8°, angle of opened leg 101,0°, angle of rotation of foot sole 50,0°, and right on the determined target.